HUBUNGAN ANTARA REALISASI DANA BANTUAN OPERASIONAL KESEHATAN DENGAN INDIKATOR GIZI KIA DI KABUPATEN/KOTA PROVINSI JAWA TENGAH TAHUN 2012 - Ulma Putri Septyantie Malik Cahyadin (Jurnal Kebijakan Kesehatan Indonesia, 2013)
Background: Health Operational Fund (HOF) is a grant fromcentral government through the Ministry of Health. The goal isto help local governments for implementing health servicesbased on Minimum Service Standards (MSS) in the field ofhealth to accelerate the achievement of the MillenniumDevelopment Goals (MDGs). Health development policies in2010-2014 are directed to enable availability of fundamemntalhelalth access that cheap and affordable especially for thelower-middle gorups. This is indicated by increasing lifeexpectancy, infant mortality and maternal mortality. One of thehealth priority programs is Nutrition Program and the Maternaland Child Health (MCH).Methods: This research is quantitative research. Analysismethod uses a simple regression. Research data are secondarydata in 2012 of 35 districts/cities in Central Java Province.Results: The realization of Health Operational Fund (HOF) issignificant ( Sig.0,000 < ±=1%) on neonatus first visit/KN1, therealization of Health Operational Fund (HOF) is significant (Sig.0,000 < ±=1%) on assistance by skilled health personnel/Pn, and the realization of Health Operational Fund (HOF) issignificant ( Sig.0,000 < ±=1%) on children weighing or D/S.Coefficient of determination (r ²) is 0.629 for the effect of HOFon KN1, 0.636 for the effect of HOF on Pn, and 0.690 for HOFon D/S. The result of classical assumptions shows that residualvariables are normally distributed, despite heteroscedasticityand despite autoccorelation.Conclusion: HOF has positive effect and significant on KN1,HOF has positive effect and significant on Pn, and HOF haspositive effect and significant on D/SKey Words: HOF, MCH Nutrition, Simple Regression, CentralJava